40 years of democracy in Argentina: A decolonial didactic sequence about our last dictatorship in the English class at Social Work College - Polastri, Vanesa (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2024)
This classroom account delves into a decolonial didactic sequence carried out in 2023 within the subject English II, corresponding to the fourth and final year of Social Work College. The sequence was developed in answer to a call made by the Dirección General de Cultura y Educación (DGCyE) to address the 40th anniversary of the restoration of democracy in Argentina with the purpose of remembering the victims from the illegal repression of the last coup d’etat and celebrating democratic values through active citizenship. The article also discusses the difficulty educators find when intending to deal with Argentinian matters in English, with regards to identity construction and the selection of materials in the target language.